2015
DOI: 10.4236/fns.2015.614137
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Habits and Body Mass Index to Female Students College Sciences and Arts Campus 1 at Khamis Mushayt King Khalid University

Abstract: Background: In the Kingdom of Saudi Arabia (KSA), recent studies revealed increasing consumption of animal products and refined foods in the diet at the expense of vegetables and fruits. These dietary changes were accused of increasing the prevalence of both overweight and obesity observed among Saudi children, adolescences and adults in the last few decades. Objectives: The present study was a cross sectional study aimed at exploring the BMI distribution among students of college of Sciences and Arts for girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation. Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…19 The prevalence rate of obesity in the current study is similar to the studies done by Majeed and Anding et al and it is slightly higher than the study done in Abha by Hakeem et al among the female college students. [26][27][28] Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation. Different studies across the globe reported various prevalence rate of overweight and obesity and that may be due to the differences in sample size and culture but still all the above described studies reveal that obesity and overweight are the major public health issue across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Con relación al estado nutricional, los resultados de este estudio apoyan la hipótesis que el conocimiento sobre alimentación y nutrición de los estudiantes universitarios está asociado negativamente con el sobrepeso y la obesidad, es decir, a mayor conocimiento en nutrición, menor será el IMC, (mayor posibilidad de ubicarse en el rango de un peso normal). Esto difiere con algunos estudios realizados en universidades en el que no encontraron relación estadística significativa entre el IMC y el conocimiento nutricional 35,36 y otro en Kuwait en el que se evidenció que los estudiantes con IMC ≥ 30 obtenían una puntuación mayor en conocimiento nutricional respecto a los que tenían bajo peso, normal o sobrepeso 33 . No obstante, aunque no utilizaron la variable IMC, Yahia et al, en un estudio reciente concluyeron que existe correlación negativa entre el conocimiento y la ingesta de grasas 37 .…”
Section: Discussionunclassified
“…Namun berbeda dengan Hasil uji korelasi chi square aktivitas fisik pada IMT normal-gemuk, menunjukkan bahwa Aktivitas Fisik mempunyai hubungan yang signifikan dengan IMT normalgemuk, dengan nilai p = 0,047 dan OR = 2.880; 95% CI: 0 .975-8.504, artinya subjek yang beraktivitas fisik ringan cenderung 3 kali lebih berisiko mempunyai IMT gemuk dibandingkan dengan orang yang melakukan aktivitas fisik sedang dan berat. Hal tersebut juga sesuai dengan hasil dari beberapa penelitian yang menyatakan ada hubungan yang signifikan antara aktivitas fisik dengan Indeks Massa Tubuh [19,20,21,22,23].…”
Section: Aktivitas Fisikunclassified